Protect Effects of Seafood-Derived Plasmalogens Against Amyloid-Beta (1–42) Induced Toxicity via Modulating the Transcripts Related to Endocytosis, Autophagy, Apoptosis, Neurotransmitter Release and Synaptic Transmission in SH-SY5Y Cells - Feng, Junli; Song, Gongshuai; Shen, Qing; Chen, Xi; Wang, Qingcheng; Guo, Shunyuan; Zhang, Manman (Frontiers in Aging Neuroscience, 2021)
To investigate the underlying mechanisms of decreased plasmalogens (Pls) levels in neurodegenerative diseases, here the effects of seafood-derived Pls on undifferentiated and differentiated human SH-SY5Y neuroblastoma cells exposed to amyloid-1-42 was analyzed. Transcriptional profiles indicated that a total of 6,581 differentially expressed genes (DEGs) were significantly identified among different experimental groups, and KEGG analysis indicated that these DEGs were related to AD, endocytosis, synaptic vesicle cycle, autophagy and cellular apoptosis. After Pls treatment, the striking expression changes of ADORA2A, ATP6V1C2, CELF6 and SLC18A2 mRNA strongly suggest that Pls exerts a beneficial role in alleviating AD pathology partly by modulating the neurotransmitter release and synaptic transmission at the transcriptional level. Besides these, GPCRs are also broadly involved in Pls-signaling in neuronal cells. These results provide evidence for supporting the potential use of Pls as an effective therapeutic approach for AD.